Implementing digital game-enhanced pedagogy: Supportive and impeding language awareness and discourse participation phenomena. Issue 1 (3rd October 2019) - McNeil, Levi
Abstract: This descriptive study investigated the implementation of student-selected, entertainment-purposed digital games for foreign language teaching and learning. During a 15-week semester, 16 Korean EFL students enrolled in an introductory educational technology course played online games, visited gaming sites, and completed instructional tasks. Conceptualizing games as social practices and drawing from the bridging activities framework (Thorne & Reinhardt, 2008), instructional tasks were designed to enhance language awareness and to present possibilities for socialization into gaming discourses. The study investigated the ways that the designed pedagogy supported or impeded language awareness and gaming discourse participation. The study found that the students exhibited language awareness in many ways, but that there were missed opportunities in developing student understandings of language as a social medium. Additionally, six students (38%) directly participated in gaming spaces, and some of them took on more central roles in gaming practices over time. Other students, however, did not attempt to directly participate in gaming sites or were not successful in their attempts. These findings are discussed in regard to pedagogical design, including game selection and supporting learner analyses of gaming discourses, as well as avenues for future research examining socialization in classrooms and gaming spaces.